Conceptual design of a blended wing body aircraft with distributed electric propulsion - Lammen, W.F.; Vankan, W.J. (Netherlands Aerospace Centre NLR, 2021)
This paper describes the conceptual design investigation for a short-medium range (SMR) aircraft. The design is aimed at a blended-wing-body (BWB) aircraft configuration with distributed electric propulsion (DEP). A fully turboelectric power train has been applied. This design study is part of the EU H2020 project IMOTHEP (Investigation and Maturation of Technologies for Hybrid Electric Propulsion) which applies a holistic approach towards design of hybrid electric propulsion aircraft. Integrated analyses of hybrid electric power train technology are performed in close connection with propulsion systems and aircraft architectures. This paper reports a selection of results of the first design loop in IMOTHEP. The results give a first indication of the potential fuel burn reduction for the BWB configuration in combination with DEP, compared to conventional SMR aircraft. Simplified power train simulation models were applied in this conceptual design loop. In follow-on design loops more refined models and data resulting from the project’s technological studies of the power train components will be applied.
This report is based on a presentation held at the MEA 2021 - More Electric Aircraft Conference, Bordeaux, 20/10/2021.